Polydatin, A Glycoside of Resveratrol, Is Better Than Resveratrol in Alleviating Non-alcoholic Fatty Liver Disease in Mice Fed a High-Fructose Diet - Zhao, Guangshan; Yang, Lian; Zhong, Wenshen; Hu, Yuze; Tan, Yu; Ren, Zhe; Ban, Qiuyan; Yang, Chung S.; Wang, Yifei; Wang, Zhiping (Frontiers in Nutrition, 2022)
Resveratrol (RES) is considered to be an activator of AMPK with many reported health benefits. Polydatin (POD) is a natural precursor and glycosylated form of RES. The glycoside structure of POD alters the bioactivity. Overnutrition and it-stimulated reactive oxygen species promote AMPK suppression and metabolic dysregulation. The present work compared the effects of POD and RES in ameliorating energy homeostasis imbalance in mice fed a high-fructose diet and elucidated the underlying mechanisms of action. Our results showed that POD elevated the fecal levels of valeric acid and caproic acid via modification of gut microbiota, while RES did not significantly influence the levels of fecal SCFAs. Both POD and RES markedly decreased oxidative stress and activated AMPK signaling pathways in the liver. POD and RES exerted a similar effect in alleviating glucose dysmetabolism, but POD was more effective in ameliorating lipid dysmetabolism than RES. Furthermore, valeric acid and caproic acid alone can activate AMPK and ameliorate hypercholesterolemia, and enhance the effects of POD on improving lipid metabolism in mice. Overall, for the first time, we demonstrated that POD administration elevated fecal levels of valeric acid and caproic acid by modifying gut microbiota thus promoting AMPK activation may be the underlying mechanism that POD is superior to resveratrol on alleviating lipid dysmetabolism. Our results suggest POD may be an alternative for RES as AMPK activator.